Analysis of Perceptions and Likes for Chicken Nugget Products among Consumers in North Kayong, West Kalimantan (Jurnal Peternakan Integratif, 2024)
Currently, there is a tendency for consumers to prefer frozen food. This study aims to analyze the perceptions and preferences of chicken nugget products on consumers in North Kayong, West Borneo. The research uses a survey method by distributing questionnaires. The perceived variables tested were price perception, quality, organoleptic, and brand. Descriptive test using a Likert scale on each perception variable is used to determine the level of consumer perception. Spearman rank correlation test is used to determine the relationship of each perception variable. Data was obtained by distributing questionnaires to 103 respondents with an age range of 15 years to 50 years and domiciled in North Kayong Regency and the sample was selected purposively. Consumers of chicken nugget products in North Kayong Regency stated that they rarely consume as much as 69%. The reason consumers like nugget products are highest on the taste aspect. Consumer perceptions of chicken nugget obtained are very good